A world history of Chinese literature - Zhang, Yingjin (Taylor & Francis Ltd, 2023)
Providing a broad introduction to the area, this book maps the field of Chinese literature across its various worlds. Looking both within - at the world of Chinese literature, its history, linguistic, cultural, local, and regional specificities - and without - at the way Chinese Literature has circulated throughout the world
Keywords: Aufsatzsammlung; Geschichte 1900-2020; Literatur; Chinesisch